Decoding the prenatal clock of sheep muscle fiber type differentiation: a temporal map from embryonic to mature types - Gu, Zhenzhen; Duan, Weiwei; Liu, Chenxi; Li, Wenrong; Zhang, Ning; Han, Bin; Liu, Mingjun (Frontiers in Cell and Developmental Biology, 2025)
BackgroundThe composition of skeletal muscle fiber types is a crucial determinant of meat quality in livestock. While the transition from embryonic to mature fiber types is known to occur during late gestation, the precise temporal dynamics and molecular mechanisms underlying this process in sheep remain poorly understood. A comprehensive, multi-technique approach is needed to elucidate the critical developmental transitions in myofiber specification.MethodsWe systematically investigated muscle fiber type differentiation in the longissimus thoracis et lumborum (LTL) muscle of sheep fetuses at 85, 105, 115, and 135 days of gestation (D85-D135) using an integrated approach combining histological (ATPase staining), protein biochemical (SDS-PAGE and Western blotting), and transcriptomic (RNA-seq) analyses. This multi-omics strategy enabled comprehensive characterization of fiber type composition, myosin heavy chain (MHC) isoform expression, and associated molecular pathways.ResultsOur findings revealed distinct stage-specific developmental patterns. Prior to D105, the number of muscle fibres increased progressively, with fibres predominantly expressing embryonic (MHC-emb) and neonatal (MHC-neo) isoforms. After D105, fibre numbers stabilized and underwent maturation, transitioning to predominantly type I, IIA, and IIB fibres, with type IIA fibres becoming the most abundant (61.2%) by D135. Transcriptome analysis identified D105 as a critical transition point, characterized by the significant downregulation of MYH3 (MHC-emb) and MYH8 (MHC-neo), and the upregulation of mature fibre genes (MYH7, MYH2, and MYH4). Concurrently, we observed increased expression of oxidative metabolism genes (COX7A1, NDUFB6) and enhanced aerobic metabolic capacity in maturing fibers.DiscussionThis study provides the first integrated multi-omics characterization of muscle fiber type development in late-gestation sheep, identifying D105 as a pivotal transition point in myofiber specification. Our findings reveal coordinated molecular and metabolic changes underlying the transition from embryonic to mature fibre types, with significant implications for understanding ruminant muscle development. These results establish a scientific foundation for improving meat quality through targeted molecular breeding strategies and prenatal nutritional interventions in sheep production systems.